ANALISA FAKTOR EXTERNAL DAN INTERNAL YANG MEMPENGARUHI NILAI PERUSAHAAN SEKTOR PERTAMBANGAN YANG TERDAFTAR DI BEI - Dipo Ananda Hendri, - (2019)
This research was conducted to analyze the effect of capital structure, liquidity, interest rates and exchange rates in influencing the value of companies in mining sector companies listed on the Indonesia Stock Exchange (IDX) for the period 2014-2017. The sampling technique used the purposive sampling method. The sample selection of 47 Mining Sector Companies listed on the Indonesia Stock Exchange in 2014-2017 produced 37 acceptable companies. Data analysis was performed using Microsoft Excel 2016 and hypothesis testing in this study used multiple linear regression analysis with the E-Views 9 program and a significance level of 5%. The results of the test are obtained (1) capital structure expressed by DER has a significant effect on firm value, (2) liquidity expressed by CR does not have a significant effect on firm value (3) the interest rate stated by the average does not significantly influence the value company, (4) the exchange rate stated in the middle exchange rate has a significant negative effect on the value of the company.